2022
DOI: 10.3389/fphys.2022.898866
|View full text |Cite
|
Sign up to set email alerts
|

Leadless Left Bundle Branch Area Pacing in Cardiac Resynchronisation Therapy: Advances, Challenges and Future Directions

Abstract: Leadless left bundle branch area pacing (LBBAP) represents the merger of two rapidly progressing areas in the field of cardiac resynchronisation therapy (CRT). It combines the attractive concepts of pacing the native conduction system to allow more physiological activation of the myocardium than conventional biventricular pacing, with the potential added benefits of avoiding long-term complications associated with transvenous leads via leadless left ventricular endocardial pacing. This perspective article will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
13
0
1
Order By: Relevance
“…Using this method, LV pacing is achieved wirelessly by converting acoustic energy to pacing energy with a receiving electrode in the LV wall (58). A meta-analysis conducted recently concluded that leadless LV pacing could serve as a second-line therapy for conventional CRT non-responders (59). In recent years, BVP has been expanded from severe HF (NYHA III/IV) to mild to moderate HF (NYHA I/II), yet HF patients with a narrow QRS (<130 ms) do not respond to it or benefit from it in most cases.…”
Section: Clinical Limitations Of Biventricular Pacing For Heart Failu...mentioning
confidence: 99%
“…Using this method, LV pacing is achieved wirelessly by converting acoustic energy to pacing energy with a receiving electrode in the LV wall (58). A meta-analysis conducted recently concluded that leadless LV pacing could serve as a second-line therapy for conventional CRT non-responders (59). In recent years, BVP has been expanded from severe HF (NYHA III/IV) to mild to moderate HF (NYHA I/II), yet HF patients with a narrow QRS (<130 ms) do not respond to it or benefit from it in most cases.…”
Section: Clinical Limitations Of Biventricular Pacing For Heart Failu...mentioning
confidence: 99%
“…Only a significant improvement in the LVEF was achieved after WiSE-CRT implantation (28.43 ± 8.01% vs. 39.71 ± 11.89%, P = 0.018) without evidence of LV reverse remodeling and improved NYHA class. A current meta-analysis of leadless LV pacing for CRT (80) included five studies (four with RV leads of conventional devices and one with Micra) involving 181 total patients in the final analysis. The success rate of the procedure was 90.6%.…”
Section: Totally Leadless Cardiac Resynchronization Therapymentioning
confidence: 99%
“…4 The WiSE CRT system. Reproduced from Wijesuriya et al [50], with permission be in part due to the development of a transseptal delivery method for the LV endocardial electrode (very common clinical practice for most electrophysiologists) as compared with large bore femoral arterial access and a retrograde aortic approach [56]. In addition, after initially high rates of pericardial effusions in the WiSE-CRT study [51], the delivery sheath was modified to subvert this complication.…”
Section: Wireless Left Ventricular Pacingmentioning
confidence: 99%
“…A combination of a transvenous pacemaker/ICD along with a leadless ultrasound-based technology for endocardial LV resynchronization has been proposed as an alternative to a coronary sinus lead in cardiac resynchronisation therapy (CRT) in the form of the WiSE-CRT device (EBR Systems Inc., Sunnyvale CA, Fig. 4 ) [ 50 ]. The system consists of three components: a submuscular transmitter under the left breast connected to a subcutaneous battery on the left side of the chest wall and an endocardial left ventricular receiver electrode.…”
Section: Wireless Left Ventricular Pacingmentioning
confidence: 99%